Pengaruh Literasi Keuangan Terhadap Pertumbuhan Usaha UMKM Di PPHY - Wildan Falikhin; Iva Khoiril Mala; Sutantri Sutantri (JOURNAL OF SHARIA ECONOMICS, 2024)
The subjects of this research are UMKM around the PPHY Lirboyo area. The method used in this research is quantitative with a descriptive research type. The sampling method was carried out using a non-probability method, saturated sampling, with a total of 35 people studied. Based on the results of hypothesis testing, financial literacy influences business growth. Based on the results of decision coefficient research, financial knowledge has a significant influence on business growth of up to 40.3%. while 59.7% was influenced by other factors not considered in this study. The financial literacy level of UMKM in HY Boarding School is classified as poor. To help UMKM develop their businesses, financial knowledge must always be improved.